HADIS TENTANG MEMBACA DOA (BASMALAH) SEBELUM MAKAN DAN MINUM SERTA RELEVANSINYA TERHADAP PEMELIHARAAN KESEHATAN (FISIK DAN MENTAL) - Sukmasari Dewi Chan (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
How important is it to read prayer (basmalah) before eating and drinking for human health? This question will describeb in this article by describing some of the related hadiths by reading prayer (basmalah) before eating and dringking and outlining the relevance of the hadith to the maintence of human health. Health in question is physical health and mental health. Reading prayers (basmalah) before eating and drinking is highly recommended. It is intended that the food and drinks consumed get blessings from Allah SWT, in addition to preventing Satan from participating in eating and drinking while consuming food and drinks. Health care contained in reading prayers (basmalah) before eating and drinking is maintenance of mental health and physical health